Engaging Purchase Decision of Customers in Marketplace Channel: A Study of Fashion Online Retail - Dewi Mustikasari Immanuel (University of Merdeka Malang, 2020)
The rapid development of internet technology has encouraged many buying and selling activities conducted online, one of which is through the marketplace. Many types of products that can be sold in certain markets only create increasingly fierce competition between markets and sellers who are members of it. Buy a variety of unique and creative promotions offered to attract consumers to buy. However, promotion is apparently not enough for products sold online, there are still many factors that can be determinants of consumer purchasing decisions. Of the many factors, this study aims to determine whether price, trust, e-WOM, social factors, product design, ease of purchase (practicality), and personal factors are factors that drive the purchase of fashion products in the marketplace. This study conducted a factor analysis with Partial Least Square (PLS). The population in this study are people who have been bought in markets such as Toopedia, Shopee, and Bukalapak who live in Surabaya. The sampling technique used was purposive sampling with 385 samples. Data collection in this study was carried out by collecting questionnaires on respondents. The results show the facts of the driving decision of the purchase of fashion products in the market place that can be sorted starting from the biggest influence starting from a trust, ease of shopping (practicality), product design, personal factors, e-WOM, price and finally social factors. Keywords: Purchase Decision, Price, Trust, E-Wom, Social Factors, Product Design, Ease of Purchase, Personal Factors